Pengaruh Pembelajaran Berbasis Masalah Kontekstual Matematika dengan Teknik Scaffolding terhadap Kemampuan Komunikasi Matematis Siswa SMA ditinjau dari Self Efficacy - M. Whyan Hafizh Ar-Rafi; Dirasti Novianti (UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
This research aims 1) to determine the differences in the mathematical communication abilities of students who are given contextual problem-based learning with scaffolding techniques and conventional learning, 2) to determine the differences in the mathematical communication abilities of students with high, medium and low self-efficacy. This research uses a quantitative approach with a quasi-experimental type of research with a pretest posttest control group research design. Data analysis techniques are descriptive statistics and inferential statistics. The results of data analysis show that 1) there are differences in the mathematical communication abilities of high school students who are taught with scaffolding and students without scaffolding. 2) there are differences in mathematical communication abilities between students who have high, medium and low self-efficacy.